DEVELOPMENT OF LEBAK UNIQUE MOBILE APPLICATION FOR SOCIAL STUDIES LEARNING IN ELEMENTARY SCHOOL TO INCREASE UNDERSTANDING AND LOVE OF LEBAK LOCAL WISDOM - HADI SUTIAWAN; AJENG GINANJAR (Edueksos : Jurnal Pendidikan Sosial & Ekonomi, 2021)
ABSTRACTThis research is motivated by technological developments and globalization which directly affect the development of lifestyles and the degradation of the understanding of local wisdom in the Lebak district. Thus, the learning revolution from offline to online has become a momentum in developing and introducing Lebak local wisdom. The implementation of this research is carried out by using the Lebak Unique mobile application in social studies learning in elementary schools, which will be a reference for teachers in carrying out online learning,especially in social studies learning that adheres to the concepts of innovation, creativity, and local wisdom. This study aims to increase students' understanding and love for Lebak local wisdom by using nonequivalent control group design research methods. The results of the statistical test showed that there was a significant difference between the classes that used the application and those that did not. Through the PostHoc LSD test, it was known that the difference between the control class and the Experimental class was -10,86861 with a significance value of 0.05, so it can be concluded that the Lebak Unique application can beutilized in the environment. Education for the development of students' understanding and love of Lebak local wisdom. Keywords: Lebak Unique; Social Studies learning; Lebak Local Wisdom.